Clinical and dermoscopic assessment of the efficacy of topical trichloroacetic acid 70% versus methoxsalen 0.2% paint in stable acral vitiligo - Elshahed, Ahmed R.; Ammar, Amr M.; Ali, Abdallah M.; Elsaie, Mohamed L. (Scientific reports, 2025)
Loss and absence of melanocytes due to a number of factors is responsible for vitiligo; known to be the commonest disorder of pigmentation. The aim of the study was to assess clinically and dermoscopically the efficacy of topical trichloroacetic acid 70% versus methoxsalen 0.2% paint in stable acral vitiligo. The patients were randomly divided into 2 groups. Group a ( n = 35) received topical 0.2% methoxsalen every other day for 4 months duration with dermoscopic follow up while group b ( n = 35) received received topical TCA 70% application at the clinic every two weeks for 4 months with dermoscopic follow up. The majority of subjects in both groups experienced either no or mild improvement. In TCA group, mean improvement was 4.0 ± 11.6% with range of 0–60% while in the methoxsalen group, mean improvement was 0.57 ± 3.3% with range of 0–20% ( p = 0.051). The majority of patients reported poor satisfaction. Both modalities did not demonstrate a significant clinical nor dermoscopic response. TCA 70% had a lower effective rate than other studies probably due to resistance of acral vitiliginous lesions to treatment in comparison to other sites of the body. Further larger multi centre studies with different concentration and combination modalities are required to detect promising treatments for vitligo.